1981
DOI: 10.1007/bf00441436
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary paracoccidioidomycosis in a nine year old girl

Abstract: A case of pulmonary paracoccidioidomycosis in a nine year old girl is reported. This is the first proven case of exclusive pulmonary paracoccidioidal lesions observed in a child. A review of the mycosis among children 0 to 10 years old is also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
1

Year Published

1983
1983
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 4 publications
0
7
0
1
Order By: Relevance
“…Even in the juvenile patients who exhibit a more acute form of the disease, the incubation period may encompass months, with no precise indications to the origin of infection [46,48].…”
Section: Facts About the Human Hostmentioning
confidence: 99%
“…Even in the juvenile patients who exhibit a more acute form of the disease, the incubation period may encompass months, with no precise indications to the origin of infection [46,48].…”
Section: Facts About the Human Hostmentioning
confidence: 99%
“…(5) Another child, who was 6 years old and had frequent contact with the rural environment, had high fever, mild bilateral interstitial pulmonary infiltrate and marked hilar lymphadenomegaly. (6) In the following weeks, this child developed disseminated fungal disease, which led to the assumption that the initial findings represented the primary lymph node complex of P. brasiliensis infection.…”
Section: Introductionmentioning
confidence: 99%
“…(3,4) The primary complex resulting from infection with P. brasiliensis has rarely been observed in children (5,6) or in immunocompromised adults.Here, we report the case of a young adult who presented with lung injury, hilar lymph node enlargement and hypereosinophilia as manifestations of the initial phase of this fungal infection. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Only 3 cases of primary pulmonary complex lesions have been retrospectively diagnosed in older patients on the basis of anatomicopathological findings [3][4][5]. There are also only a few reports of younger individuals who have presented with a pulmonary syndrome resembling a primary pulmonary lymph node complex [6][7][8]. It has been shown that even patients who have the acute form of PCM with no respiratory symptoms and with normal findings on chest radiographs may have their lungs colonized with the fungus [9].…”
mentioning
confidence: 99%